Enhanced Electro-Degradation of Direct Black 38 Dye Using Copper Oxide–Modified Graphite Electrode and CaCl₂ as Supporting Electrolyte - Siti Marwati; Regina Tutik Padmaningrum; Isana Supiah Yosephine Louise; Grandis Wahyuning Dewandaru (Jurnal Kimia Sains dan Aplikasi, 2026)
The dyes used in the textile industry generate substantial waste, posing significant environmental hazards. Because textile industries discharge large amounts of effluents, it is essential to develop effective methods to reduce the presence of reactive textile dyes. This work evaluated the removal of Direct Black 38 (DB-38) using the bare graphite electrode (GE) modified by copper oxide to form a graphite/Cu/Cu-oxide (GE/Cu/Cu-oxide). The electrode was prepared by electrodeposition. Electro-degradation of 50 ppm DB-38 dye was conducted at different applied potentials, reaction times, and CaCl2 concentrations as supporting electrolytes. The X-ray diffraction patterns showed the highest peak at 2θ = 36.55, corresponding to graphite/Cu2O, and at 2θ = 38.73, corresponding to graphite/CuO. The GE/Cu/Cu-oxide electrode is eleven times more reactive than bare graphite. The GE/Cu/Cu-oxide electrode achieved a 99.08% electro-degradation efficiency of DB-38, with a reduction of 97.50% in COD, and 40.60% in TDS after 60 minutes, when 0.03 M CaCl2 was used as the supporting electrolyte at a potential 12 V. Thus, the proposed process demonstrated promising results for dye treatment in various aqueous matrices, utilizing low-cost, readily available electrodes that have not been previously applied for this purpose.